Simulation of wire and arc additive manufacturing of 308L stainless steel with cold arc gas metal arc welding / Nur Izan Syahriah Hussein ... [et al.] - Hussein, Nur Izan Syahriah; Mohd Jmmani, Nur Aisyah Nabilah; Ayof, Mohamad Nizam; Abd Rahim, Toibah; Zainal Abidin, Muhammad Zaimi; Yusof, Farazila; Jamaludin, Mohd Fadzil; Willliams, Stewart (Smart Manufacturing Research Institute (SMRI), 2021)
This research focuses on the capabilities of coldArc GMAW in the behavior of heat input to the weld bead dimension. In this study, the effect of process GMAW of 308L stainless steel filler wire with a thickness of 1.2 mm and 304L stainless steel base plate, with a dimension of 120 mm x 25 mm x 10 mm (height x width x thickness) by applying WAAM. The data was collected using MATLAB of a Smart Weld Rosenthal's Steady-State 3D Isotherms. A Taguchi response was used in the DOE method with Minitab software to analyze the effect of process parameters on height, width, and depth of weld bead dimension during GMAW. The experiments were conducted following the low, mid, and high input parameters will show the different structures of weld bead dimension, which include 70 A, 75 A, and 78 A (arc current), 15 V, 16 V, and 17 V (voltage), 400 mm/min, 600 mm/min, and 800 mm/min (welding speed). Hence, the optimum value is 75 A, 16 V, and 800 mm/min, and the most significant parameters to deposit stainless steel with coldArc GMAW were welding speed followed by arc current and voltage.